Nursing management of a patient with kawasaki disease complicated with acute myocardial infarction (1例川崎病并发急性心肌梗死患者的护理体会) - LUO Fang (罗芳); SONG Mi (宋咪) (Association of Integrative Nursing, 2022)
This paper summarized the nursing management of a patient with Kawasaki disease complicated with acute myocardial infarction. Key issues of nursing included illness observation, perioperative nursing of emergent intervention, psychological nursing, health education, and so on. (本文总结1例川崎病(KD)并发冠状动脉瘤样病变形成血栓导致心肌梗死患者的护理经验, 包括病情观察、急诊介入术围手术期的护理、心理护理、健康教育等。)